Hubungan Karakteristik Sosial Demografi dan Literasi Kesehatan Dengan Kepatuhan Minum Obat Pada Penderita Tuberkulosis di Kota Kupang - Nailius, Imelda Sussanti; Anshari, Dien (Perilaku dan Promosi Kesehatan : Indonesian Journal of Health Promotion and Behavior, 2022)
Bakground. Success rate for tuberculosis treatment in Kupang City was reported in the last four years to be at an average of 82.1%, which has not reached the national target of 90%. One of the reasons for the failure was due to the long period of taking the medication which made it possible for non-adherence to take the medication. Noncompliance with medication might result in treatment failure, re-treatment, or drug resistance. Aim. to determine the relationship between social demographic characteristics and health literacy and tuberculosis medication adherence in Kupang City. Method. This study employed quantitative study with cross-sectional design. Data was obtained by filling out online questionnaires (self-administered surveys) on 126 tuberculosis patients receiving treatment at 11 health centers in Kupang City. The data was examined using simple logistic regression and multiple logistic regression. Result. Results showed that 23.8 percent of tuberculosis patients were disobedient in taking tuberculosis medications. Health literacy characteristics (p=0,008, OR=10,4, CI: 1,847-59,17) and respondent age (p=0,029, OR=0,2, CI: 0,070-0,863) with p-values 0.05 were found to be substantially related to tuberculosis patients' medication adherence. Conclusion. Health literacy is the most dominant variable in influencing medication adherence for tuberculosis patients after being controlled by age, education, and income.